PIS BOLONG POSTER DESIGN: THE ACCULTURATION OF CHINESE AND BALINESE CULTURE IN INDONESIA - Rai, I Gusti Ngurah Tri Marutama; Adi, Sigit Purnomo; Taemprasit, Somporn (ISI Press Institut Seni Indonesia Surakarta, 2024)
This study explores the integration of Chinese and Balinese cultural elements in poster design as a means of visual communication. This study aims to understand how cultural acculturation is manifested in poster design by integrating visual idioms from both cultures to convey messages of solidarity, tolerance, and cultural appreciation and preservation. Using qualitative research and a Design Thinking approach, this study seeks to present cultural acculturation values in poster design elements and evaluate their impact on the audience. The research findings demonstrate that the combination of Chinese and Balinese cultural symbols, colors, and patterns effectively produced a communicative and aesthetically appealing visual narrative. These findings highlight the significance of cultural comprehension in visual communication design and contribute to the development of culture-based design practices. This study enhances our understanding of the function of design in communicating cultural values.